Design and Development of an Internet of Things (IoT)- Based Prototype Drainage Water Level Monitoring System for Oil Palm Plantations - Rohatul Qolby; Siti Dinar Rezki Ramadhani; Riri Nasirly; Nurul Qolbi El Azizah; Fadly Arsi; Widya Laila (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Oil palm plantations require effective drainage management systems to maintain stable water levels and prevent waterlogging and flooding that can negatively affect crop productivity. Conventional manual water level monitoring has limitations in terms of speed, accuracy, and real-time information availability. This study aims to design and develop an Internet of Things (IoT)-based water level monitoring system for drainage channels in oil palm plantations. The proposed system utilizes an ESP32 microcontroller as the main processing unit, an HC-SR04 ultrasonic sensor for water level measurement, and the MQTT protocol for data communication. The measured data are transmitted in real time to a web-based dashboard, enabling remote monitoring and rapid decision- making. The research methodology consists of system requirements analysis system design, hardware and software implementation, as well as system testing and validation. The results demonstrate that the system successfully measures and transmits water level data every two seconds with an average communication delay of less than two seconds. Sensor accuracy testing shows an average measurement error of approximately ±0.3 cm compared to manual measurements. The system is also equipped with LED indicators and a buzzer that operate according to predefined alert levels, namely safe, warning, and emergency conditions. Furthermore, the web dashboard provides responsive real-time visualization of water level information. Overall, the developed system offers a modern, accurate, and efficient solution for drainage monitoring, supporting water management and early flood mitigation efforts in oil palm plantation environments.